2019
DOI: 10.1038/s41586-019-1400-3
|View full text |Cite
|
Sign up to set email alerts
|

H+ transport is an integral function of the mitochondrial ADP/ATP carrier

Abstract: SUMMARY The mitochondrial ADP/ATP carrier (AAC) is a major transport protein of the inner mitochondrial membrane. It exchanges mitochondrial ATP for cytosolic ADP and controls cellular ATP production. In addition, AAC may mediate mitochondrial uncoupling, but this AAC function and its mechanisms remain elusive. Here we record AAC currents directly from inner mitochondrial membrane of various tissues and identify two distinct transport modes: ADP/ATP exchange and H + transport.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
249
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 217 publications
(267 citation statements)
references
References 52 publications
16
249
2
Order By: Relevance
“…SS-31 binding to the ADT channel yet not functioning as an ADT inhibitor opens the possibility of therapeutic alteration of the balance of conformational states, potentially modulating proton leak and ADP/ATP exchange. As proposed in the recent report, the mechanism of proton leak through ADT is dependent on electrostatic interactions of the positively charged substrate binding site with a fatty acid (FA) co-factor, and competes with nucleotide transport through ADT [65]. Likewise, one can hypothesize that proton leak is prevented possibly through charge repulsion via two positively charged residues (Arginine and Lysine) in SS-31 ( Fig.…”
Section: Atp Production and Transport (Cv Ck And Adt)mentioning
confidence: 85%
See 2 more Smart Citations
“…SS-31 binding to the ADT channel yet not functioning as an ADT inhibitor opens the possibility of therapeutic alteration of the balance of conformational states, potentially modulating proton leak and ADP/ATP exchange. As proposed in the recent report, the mechanism of proton leak through ADT is dependent on electrostatic interactions of the positively charged substrate binding site with a fatty acid (FA) co-factor, and competes with nucleotide transport through ADT [65]. Likewise, one can hypothesize that proton leak is prevented possibly through charge repulsion via two positively charged residues (Arginine and Lysine) in SS-31 ( Fig.…”
Section: Atp Production and Transport (Cv Ck And Adt)mentioning
confidence: 85%
“…Importantly, ADT was recently identified to support two distinct and competing transport modes involving ADP/ATP exchange and proton leak and thus, ADT connects coupled and uncoupled energy conversion mechanisms in mitochondria, respectively [65]. Studies have shown that proton leak through ADT was elevated in aged mitochondria and impairment of ADT was believed to play a central mechanism causing aged-related mitochondria defects [66][67][68].…”
Section: Atp Production and Transport (Cv Ck And Adt)mentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests a role for other mechanisms that may also mediate proton leak, independent of UCPs. Notably, recent observations suggest that mitochondrial ADP/ATP carriers, also activated by FA, may be responsible for FA‐induced increase in leak respiration.…”
Section: Pathophysiology Of Disturbances In Mitochondrial Metabolismmentioning
confidence: 99%
“…The debate regarding the capacity of UCPs to uncouple mitochondria in the heart and the extent to which UCP3 is involved in the prevention of ROS formation remains unsettled. However, the correlation between UCP3 levels and FAO in the heart under obese/diabetic conditions does support a role for UCP3 under conditions of perturbed cardiac energy balance .…”
Section: Pathophysiology Of Disturbances In Mitochondrial Metabolismmentioning
confidence: 99%